Telemedicine in stroke care - Breuer, Lorenz; Schwab, Sibylle (Medizinische Klinik - Intensivmedizin und Notfallmedizin, 2017)
Telemedicine is already widely used in many telestroke networks and ensures stroke treatment close to the patient's home in rural and medically underserved areas. This is particularly effective when telemedicine is integrated into a stroke unit concept. While telemedically based thrombolysis therapy has become routine practice for many years, practical implementation of comprehensive mechanical thrombectomy and the related processes remains challenging. The main tasks for the future further include development of a structured stroke aftercare system in neurologically underserved areas and permanent assurance of high-quality stroke care in telemedically connected sites.
EVALuna2:22560